Boosting inter-organizational creativity in the hotel industry during the coronavirus crisis: The driving role of relational factors - Leonidou, Leonidas C.; Aykol, Bilge; Fotiadis, Thomas A.; Marinova, Svetla; Christodoulides, Paul (My University, 2022)
Anchored on the Circumplex Model and Broaden-and-Build Theory, we develop and test a conceptual model in which satisfaction, influenced by communication, cooperation, conflict and opportunism, is set as the driver of inter-partner creativity in the relationship between hotels and their foreign travel agents under the Covid-19 pandemic. Our model was tested with SEM analysis, using data collected from 190 randomly selected hotel units located in Greece through an online or drop-in self-administered questionnaire. The results revealed that satisfaction with the working relationship with the foreign partner during this crisis situation can be enhanced by improving communication and cooperation between interacting parties, but diminished by the existence of incidences of conflict and opportunism. Satisfaction was also found to be a strong predictor of inter-partner creativity during these critical times, although this was less profound under high levels of distance and rigidity in the relationship.
Keywords: Covid-19 pandemic; Crisis management; Inter-partner creativity